STRATEGIES AND CHALLENGES OF ICT INTEGRATION IN ENGLISH LANGUAGE LEARNING AT SMP NEGERI 2 SRAGEN, CENTRAL JAVA - Evananda Shinta Clarinfa; Nur Hidayat (English Education Department at FKIP Nommensen University, 2026)
The incorporation of Information and Communication Technology (ICT) is vital for raising the quality of English language education, especially in increasing student involvement and accessibility to learning resources. Nonetheless, its execution also poses certain educational and technical difficulties. This study aims to analyze students' opinions of ICT utilization in English learning, investigate instructors' instructional methodologies, and identify obstacles to its implementation at SMP Negeri 2 Sragen, Central Java. This research utilized a mixed-methods approach including a sequential explanatory design. Quantitative data were gathered from 131 ninth-grade students via a 19-item questionnaire, while qualitative data were acquired through semi-structured interviews with three English instructors. The quantitative data were examined by descriptive statistics, and the qualitative data were determined via theme analysis. The results demonstrate that students mainly possess favorable views toward ICT integration, evidenced by mean scores between 1.85 and 2.13 for ICT advantages and 1.70 to 2.42 for student expectations. Information and Communication Technology (ICT) was determined to improve students' motivation, vocabulary development, and understanding, especially in listening and reading abilities. Educators employed several ICT resources, including Google Forms, Quizizz, PowerPoint, projectors, and AI-driven applications, to facilitate student-centered learning. Nonetheless, other concerns were recognized, such as inadequate infrastructure, unreliable internet connectivity, disparities in students' digital competence, classroom management difficulties, and students' overdependence on technology. In summary, the incorporation of ICT enhances student engagement and language acquisition; yet, its efficacy is contingent upon pedagogical design, students' digital proficiency, and institutional backing. Consequently, a more deliberate and equitable use of ICT is necessary to maximize its advantages in English language acquisition.